Analysis of the efficiency of Higher Education in Colombia by department from the incoming variables coverage and enrollment (2022)
The purpose of the following article is to analyze the efficiency of higher education in Colombia by departments specifically in the incoming and outgoing variables of Higher Education institutions in the departments of Colombia in the years 2013, 2015, 2017 and 2019 that are part of the measurement of efficiency, it can be concluded that the variable of coverage rate in higher education at the departmental level during the years of study and its percentage representation in each department involved, the department with the highest coverage rate is the district of Bogota, being the only one that is part of the range of 66% to 100%,followed by departments in the range of 33% to 66%, represented by 14 departments such as: Quindío, Santander, Risaralda, Boyacá, Atlántico, Antioquia, Caldas, Norte de Santander, Valle del Cauca, Tolima, Bolívar, Huila, Meta and Cauca, but the highest concentration is in the 10% to 33% range, made up of 14 departments comprising Guaviare, Cesar, Magdalena, Cundinamarca, Caquetá, SanAndrés, Sucre, Choco, Nariño, Casanare, Córdoba, La guajira, Arauca and Guainía.